Administrative and Public Verifiability: Can We Have Both? - Benaloh, Josh (Proceedings of the 2008 Electronic Voting Technology Workshop (EVT '08), 2008)
Administrative verifiability gives election officials the means to protect against certain kinds of errors and fraud. This is typically accomplished with tools like paper audit trails that enable manual recounts and spot checks. Public verifiability uses cryptographic and related tools to enable any member of the public to independently fully verify the accuracy of an election tally. Although public verifiability is technically a higher standard, its complexity makes it unappealing for many. This raises the question of whether it is possible to achieve public verifiability without sacrificing the traditional administrative verifiability tools in common use.